2021
DOI: 10.3389/fphy.2021.781688
|View full text |Cite
|
Sign up to set email alerts
|

Generation and Propagation of Partially Coherent Power-Exponent-Phase Vortex Beam

Abstract: We report on a partially coherent power-exponent-phase vortex beam (PC-PEPV), whose spatial coherence is controllable and the initial phase exhibits a periodic power exponential change. The PC-PEPV beam was generated experimentally with various spatial coherence widths, and its propagation properties were studied both numerically and experimentally. By modulating the topological charge (TC) and power order of the PC-PEPV beam, the structure of the vortex beam can be adjusted from circular to elliptic, triangul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…These include composite beams achieved through multi-channel superposition 18,19 , generation and manipulation of vortices using metasurfaces 20,21 , and other approaches. Recently, unconventional OV configurations have gained attention, such as power-exponent-phase vortex (PEPV) [22][23][24] , multiplexed generalized vortex beams 25,26 , and the generation of multiple twisted beams through azimuthal shift factors 27 . Some studies have also investigated the optical forces generated by phase gradients 28 .…”
Section: Introductionmentioning
confidence: 99%
“…These include composite beams achieved through multi-channel superposition 18,19 , generation and manipulation of vortices using metasurfaces 20,21 , and other approaches. Recently, unconventional OV configurations have gained attention, such as power-exponent-phase vortex (PEPV) [22][23][24] , multiplexed generalized vortex beams 25,26 , and the generation of multiple twisted beams through azimuthal shift factors 27 . Some studies have also investigated the optical forces generated by phase gradients 28 .…”
Section: Introductionmentioning
confidence: 99%
“…The spiral intensity of these beams is modulated by the exponential phase term, resulting in an uneven spiral phase gradient [26,27]. The phase of the beam specifically exhibits an exponential increase along a closed path near the central point [28]. Recent studies have explored the propagation of the power index phase vortex of a Gaussian beam within a paraxial ABCD system [23].…”
Section: Introductionmentioning
confidence: 99%
“…Various modulation methods have been explored for OV carrying OAM, such as using multi-channel superposition to obtain composite beams [19,20] , metasurface generation, and manipulation of vortices [21,22] . Recently, some more unconventional vortex beams have been proposed, such as the powerexponent-phase vortex (PEPV) beams [23][24][25] , multiplexed generalized vortex beams [26,27] , and the generation of multi-twisted beams via azimuthal shift factors [28] . Although some studies have demonstrated that phase gradients (PGs) can generate optical force [29] , research on the unique effects of different PG directions on vortex beams is severely limited.…”
Section: Introductionmentioning
confidence: 99%